C‐Mpl Is Expressed on Osteoblasts and Osteoclasts and Is Important in Regulating Skeletal Homeostasis. Issue 4 (6th October 2015) - Meijome, Tomas E.; Baughman, Jenna T.; Hooker, R. Adam; Cheng, Ying‐Hua; Ciovacco, Wendy A.; Balamohan, Sanjeev M.; Srinivasan, Trishya L.; Chitteti, Brahmananda R.; Eleniste, Pierre P.; Horowitz, Mark C.; Srour, Edward F.; Bruzzaniti, Angela; et al.
ABSTRACT: C‐Mpl is the receptor for thrombopoietin (TPO), the main megakaryocyte (MK) growth factor, and c‐Mpl is believed to be expressed on cells of the hematopoietic lineage. As MKs have been shown to enhance bone formation, it may be expected that mice in which c‐Mpl was globally knocked out (c‐Mpl −/− mice) would have decreased bone mass because they have fewer MKs. Instead, c‐Mpl −/− mice have a higher bone mass than WT controls. Using c‐Mpl −/− mice we investigated the basis for this discrepancy and discovered that c‐Mpl is expressed on both osteoblasts (OBs) and osteoclasts (OCs), an unexpected finding that prompted us to examine further how c‐Mpl regulates bone. Static and dynamic bone histomorphometry parameters suggest that c‐Mpl deficiency results in a net gain in bone volume with increases in OBs and OCs. In vitro, a higher percentage of c‐Mpl −/− OBs were in active phases of the cell cycle, leading to an increased number of OBs. No difference in OB differentiation was observed in vitro as examined by real‐time PCR and functional assays. In co‐culture systems, which allow for the interaction between OBs and OC progenitors, c‐Mpl −/− OBs enhanced osteoclastogenesis. Two of the major signaling pathways by which OBs regulate osteoclastogenesis, MCSF/OPG/RANKL and EphrinB2‐EphB2/B4, were unaffected in c‐Mpl −/− OBs. These data provide new findings for the role of MKs and c‐Mpl expression in bone and may provide insight into the homeostatic regulation of bone mass as well as bone loss diseases such as osteoporosis. J. Cell. Biochem. 117: 959–969, 2016. © 2015 Wiley Periodicals, Inc.